Inter-sentential and intra-sentential code switching in parliamentary debate / Shafiyah Mohamad Khalil and Mohammad Shazie Zaini Mohd Shahril Firda - Mohamad Khalil, Shafiyah; Mohd Shahril Firda, Mohammad Shazie Zaini (Universiti Teknologi MARA Shah Alam, 2018)
Malaysians generally use two languages which are Malay and English in professional discourse. Bahasa Melayu or the Malay language is the national language of Malaysia and is used in formal discourse in government administration, while English is the nation's second language that is used in professional discourse in private organizations in Malaysia. Although the use of English in government administration has been a hotly debated topic, but in reality both languages are used interchangeably since many Malaysian professionals are bilinguals of Malay and English. This paper has looked into two types of code-switching and how it is used in a Malaysian parliamentary debate. The findings revealed that inter-sentential and intra-sentential code-switching were used during the parliamentary debate due to social factors as well as linguistic elements.